Pendidikan Kesehatan Berbasis Komunitas Untuk Pencegahan Dan Pengendalian Hipertensi Bagi Lansia - Novikasari, Chandra; Paizal, Darma Sari; Sunata, Letra; Andeka, Loki; Agustina, Rahayu; Wulandari, Wulandari (Jurnal Dehasen Untuk Negeri, 2026)
Hypertension is nicknamed the “Silent Killer” because it is a disease without typical signs and symptoms. Because it can cause a risk of death if the diastolic blood pressure in the body increases >140 mmHg and systolic blood pressure is at >90 mmHg and exceeds the normal limit (Manimala, 2015). WHO recorded that hypertension attacks 22% of the world's population annually, and reaches 36% of the incidence rate in Southeast Asia and Indonesia is the highest with a figure of 2397% of the total 1.7 million deaths in 2019 (WHO, 2021). This condition occurs when blood vessels receive higher pressure than they should, so the heart must work harder to pump blood throughout the body. According to the Ministry of Health (Kemenkes), hypertension is a condition of high blood pressure in which the systolic pressure (top number) is more than or equal to 140 mmHg and/or diastolic pressure (bottom number) is more than or equal to 90 mmHg. The impact of hypertension can cause symptoms, and can lead to various serious complications, including: Heart disease, stroke, kidney damage, impaired vision, blood vessel damage (aneurysm), sexual disorders, and metabolic problems.